The influence of compensation, competence, and the work environment on employee performance at the Al Irsyad Islamic Education Foundation in Banten - Sherly Indria Budianda; Mohamad Irfan; Mardani Mardani; John Chaidir; Haerofiatna Haerofiatna (Enrichment : Journal of Management, 2026)
This study was conducted at the Al Irsyad Islamic Education Foundation in Banten, an educational institution that seeks to enhance employee performance in order to remain competitive with other foundations, both at the provincial level of Banten and specifically within Serang Regency. The research focuses on analyzing the influence of compensation, competence, and the work environment on employee performance. The objective of the study is to examine, describe, and provide empirical insights regarding the effects of these three variables. A quantitative research design was applied, employing various statistical procedures, including validity and reliability tests, normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, the coefficient of determination (R²), as well as partial (t-test) and simultaneous (F-test) hypothesis testing. The research population comprised all employees of the Al Irsyad Islamic Education Foundation in Banten, with a total of 62 respondents. Data were collected using structured questionnaires and supported by interviews to obtain a more comprehensive understanding of employee perceptions and working conditions. The data were analyzed using SPSS version 25. The findings reveal that compensation, competence, and the work environment each have a positive and statistically significant effect on employee performance. Furthermore, the simultaneous test results indicate that these three variables collectively contribute significantly to improving employee performance. Based on these findings, the study recommends that the foundation consistently enhance compensation systems, employee competencies, and the quality of the work environment to achieve superior performance and more effectively attain organizational objectives.